Labour inclusion of LGBTI people in Spain: Ethics and conduct codes - Rivera-Martin, Beatriz; Martínez de Bartolomé Rincón, Ireide (Ramon Llull Journal of Applied Ethics, 2023)
The company is a social agent that contributes to the integration of people in their working and social environment. Through codes of conduct, companies set out their values and ethics with the aim of guiding coexistence among the members of the corporation and, at the same time, projecting a certain external image. As argued, LGBTI people continue to suffer discrimination at work in Spain, and a high percentage of them decide to hide their sexual orientation or gender identity to avoid being excluded, which means that they do not find in their workplaces the ideal environment to feel integrated. As discussed in the theoretical framework, the willingness of governments to establish a regulatory framework for the protection of LGBTI people is not enough. Although governments are the main guarantors of the enforcement of human rights, companies have an ethical responsibility to ensure the protection of their workers in the workplace, as stated in the Universal Declaration of Human Rights, as well as contributing to social change. In short, companies should promote working conditions that avoid discrimination on the grounds of sexual orientation and gender identity and/or expression, and at the same time they should establish specific procedures for its prevention and for dealing with complaints that may be made by those who have been subjected to it. To this end, measures such as codes of conduct can be put in place. The codes of conduct of the Ibex35 companies have been analysed to reveal whether they recognise LGBTI people and in which terms. Without wishing to anticipate the final conclusions, readers are warned that they will find relevant data, and that there is still a long way to achieve the effective inclusion of LGBTI people and their different forms.
Keywords: code of conduct; ethical code; Ibex35; labour inclusion; LGBTI; Scopus